Transformasi Pluralisme Dalam Agama Buddha: Buddhayana Sebagai Bhinneka Tunggal Ika - Selwen, Panir; Kumari, Winja (Kamaya: Jurnal Ilmu Agama, 2024)
Buddhism originates from a single source and can be adapted to various circumstances and spread in various regions with various languages ​​to different tribes, peoples, times and environments. This allowed Buddhism to develop into different forms and figures. This research aims to understand that diversity and pluralism in Buddhism can be seen and understood through the concept of Buddhayana. Buddhayana is an understanding that is non-sectarian, inclusive, universal and sees differences as the wealth of Buddhism so that it can be studied according to the intelligence of every Buddhist. The method used to write this research uses a qualitative research method through a descriptive approach and data obtained from literature review. In this study, the found that understanding pluralism in Buddhism requires the application of Buddhayana values, namely inclusiveness, non-sectarianism, contextualism, and respect for pluralism and universalism. Buddhayana's values ​​are in line with the understanding and application of Unity in Diversity in Indonesia.